Users’ engagement in learning information systems: an experimental approach based on a gamification artifact - Inocêncio, Fabrício de Carvalho (2020)
Gamification systems have potential to foster students’ engagement and enhance their learning performance. Although the literature so far has provided relevant contributions in explaining how gamification design can be effective, it still strives to address properly the constructs used to measure the gamification effect, reflecting in poor performance results. This research aims provide a comprehensive picture about gamification effects on user’s outcomes and constructs, in the learning/training context. We extended the framework of Liu et al. (2017) that classifies the effect of gamification in experiential outcomes and instrumental outcomes. To do so, we performed a systematic literature review to identify the relevant constructs applied in the gamification field and we developed a gamification artifact to empirically validate the chain of gamification outcomes in two distinct studies. Our findings suggest an intermediate layer, as a study behavior, between experiential outcomes and instrumental outcome. We suggest that gamification elements affect emotional and cognitive engagement, as experiential outcomes. These outcomes will affect behavioral engagement (intermediate layer), that will affect learning performance consequently, as instrumental and final outcome. We argue that the right chain of outcomes should be addressed to accurately evaluate the effectiveness of gamification on learners and wrong or random choices can lead to poor results or inclusive analysis. We expect that the findings provided in this research can contribute to the development of successful gamification systems.